Nodulation capacity in legume forest species (Fabaceae) according to their phylogeny and morphological characteristics - de Bedout-Mora, Marianne (2022)
A large part of the success of legume plants (Fabaceae) in the different ecosystems of Costa Rica could be due to their ability to establish symbiotic relationships with microorganisms of the Rhizobiaceae family and to the fixed nitrogen that these bacteria can provide them. In this work, we evaluated the presence of nodules, the tissue where nitrogen fixation is carried out, in 24 forest species of legumes belonging to four subfamilies of Fabaceae, and several morphological characteristics of the roots were determined. The presence of nodules was detected in 14 of the 24 species (58.3%); however, there were large differences between the subfamilies. In the two subfamilies considered the most basal (Detarioideae and Cercidoideae), no nodules were detected. In the Caesalpinioideae subfamily, nodules were reported in 58.3% of the species, mostly restricted to the clade Mimosoideae. In the Papilionoideae family, considered the most derived, the presence of nodules was observed in 87.5% of the evaluated species. Most species with nodules had a light coloration on their roots, and species without nodules had a darker coloration, with some exceptions. These trends are related to the phylogenetic history of the subfamilies and the origins of nodulation. However, they could also respond to different infection mechanisms and could even be related to physiological characteristics of plants, such as the production of secondary inhibitory compounds of the nodulation. In this way, this study constitutes the first step to understand better the interactions between nitrogen-fixing microorganisms with their hosts.